Cationic Lipid Derived from a Basic Amino Acid: Design and Synthesis - Bravo Estupiñan, Diana (2024)
One of the major challenges in gene therapy is the efficient and safe introduction of nucleic acids into eukaryotic cells. This process requires overcoming various biological barriers and navigating complex pathways to reach target cells and achieve their biological function. To address this obstacle, numerous transfection methods have been developed, including physical techniques and the use of genetic vectors, both viral and non-viral. However, to date, no transfection method is 100% safe and efficient. Within the spectrum of non-viral genetic vectors, cationic liposomes formed by cationic lipids stand out for their ability to protect and deliver therapeutic NA. These liposomes offer greater biocompatibility and lower immunogenicity compared to viral vectors, although they still do not match the efficiency of viral delivery systems. Consequently, ongoing research focuses on synthesizing a wide variety of cationic lipids in the search for compounds that provide high transfection efficiency with minimal cytotoxicity. This study aimed to design and synthesize a novel cationic lipid (CholCadLys) derived from natural cellular molecules for transferring genetic material to eukaryotic cells. The lipid was synthesized using cholesteryl chloroformate for the hydrophobic region, cadaverine as a linker, and lysine for the polar region, connected by carbamate and amide bonds, respectively. Identification was confirmed through thin-layer chromatography, purification through preparative chromatography, and characterization via infrared spectroscopy and mass spectrometry. The synthesis yielded a 60% success rate, with stable nanoliposomes averaging 76 nm in diameter. Liposomes were formed using this CL and commercial neutral lipids, characterized by transmission electron microscopy and Nanoparticle Tracking Analysis. These liposomes, combined with plasmid DNA, formed lipoplexes used to transfect Hek-293 FT cells, achieving up to 40% transfection efficiency without cytotoxicity in the mixture of CholCadLys and CholCad. This novel CL demonstrates potential as an efficient, safe, and cost-effective gene transfer system, facilitating further development in gene therapy